Об упругом ударе - Герман, Эдуард Евгеньевич; Кныш, В. А.; Ушамирский, Б. А. (НТУ "ХПИ", 2004)
This paper reports about development of engineering methods for mechanic systems by impingement attack. The base of investigation consists on energy balance method. Duration of shock, maximum contact efforts and strain items in impingement items define by law of conservation of mechanical energy. Elastic impact of rod and sphere on absolute stiff barrier and percussion interaction of two moving rod be described. Method proposed in this paper permits to get the simple compute dependent, convenient to engineering application. Theoretic results are compared with experiment and trust of entry theoretic prerequisites is supported. Model of elastic impact proposed in the paper can be used for not great speeds of item in the moment of impingement.
Keywords: теория упругости; статистические зависимости; энергетический баланс; длительность контакта; максимальная сила; период колебания тел